Sold on language how advertisers talk to you and what this says about you - Sedivy, Julie; Carlson, Greg N. 1948- (Chichester, West Sussex, United Kingdom Wiley-Blackwell, 2011)
Sold on language examines how the competitive marketplace shapes the ways in which commercial and political advertisers speak to us.: Authored by a team of highly respected language scientists; Written in an informal style with many examples drawn from popular culture; Communicates ideas and research findings about language and the mind, revealing the mental processes behind the daily interactions we all have with contemporary advertising; Brings together insights from fields as varied as linguistics, philosophy, social psychology, behavioral economics, and political science.
The power of choice. -- The unconscious consumer. -- The attentional arms race. -- We know what you're thinking. -- Why ads don't say what they mean (or mean what they say). -- Acting out. -- Divide and conquer. -- The politics of choice.
Includes bibliographical references (pages [291]-305) and index.
Keywords: Advertising -- Language; Advertising